Crimean-Congo Hemorrhagic Fever Virus-Infected Hepatocytes Induce ER-Stress and Apoptosis Crosstalk - Rodrigues, Raquel; Paranhos-Baccalà, Gláucia; Vernet, Guy; Peyrefitte, Christophe N. (PLOS ONE, 2012)
Crimean-Congo hemorrhagic fever virus (CCHFV) is a widely distributed tick-borne member of the Nairovirus genus (Bunyaviridae) with a high mortality rate in humans. CCHFV induces a severe disease in infected patients that includes, among other symptoms, massive liver necrosis and failure. The interaction between liver cells and CCHFV is therefore important for understanding the pathogenesis of this disease. Here, we described the in vitro CCHFV-infection and -replication in the hepatocyte cell line, Huh7, and the induced cellular and molecular response modulation. We found that CCHFV was able to infect and replicate to high titres and to induce a cytopathic effect (CPE). We also observed by flow cytometry and real time quantitative RT-PCR evidence of apoptosis, with the participation of the mitochondrial pathway. On the other hand, we showed that the replication of CCHFV in hepatocytes was able to interfere with the death receptor pathway of apoptosis. Furthermore, we found in CCHFV-infected cells the over-expression of PUMA, Noxa and CHOP suggesting the crosstalk between the ER-stress and mitochondrial apoptosis. By ELISA, we observed an increase of IL-8 in response to viral replication; however apoptosis was shown to be independent from IL-8 secretion. When we compared the induced cellular response between CCHFV and DUGV, a mild or non-pathogenic Nairovirus for humans, we found that the most striking difference was the absence of CPE and apoptosis. Despite the XBP1 splicing and PERK gene expression induced by DUGV, no ER-stress and apoptosis crosstalk was observed. Overall, these results suggest that CCHFV is able to induce ER-stress, activate inflammatory mediators and modulate both mitochondrial and death receptor pathways of apoptosis in hepatocyte cells, which may, in part, explain the role of the liver in the pathogenesis of CCHFV.